Model-Updated Image-Guided Neurosurgery Using the Finite Element Method: Incorporation of the Falx Cerebri - Miga, Michael I. (Med Image Comput Comput Assist Interv, 1999)
Surgeons using neuronavigation have realized the value of image guidance for feature recognition as well as for the precise application of surgical instruments. Recently, there has been a growing concern about the extent of intraoperative misregistration due to tissue deformation. Intraoperative imaging is currently under evaluation but limitations related to cost effectiveness and image clarity have made its wide spread adoption uncertain. As a result, computational model-guided techniques have generated considerable appeal as an alternative approach. In this paper, we report our initial experience with enhancing our brain deformation model by explicitly adding the falx cerebri. The simulations reported show significant differences in subsurface deformation with the falx serving to damp the communication of displacement between hemispheres by as much as 4 mm. Additionally, these calculations, based on a human clinical case, demonstrate that while cortical shift predictions correlate well with various forms of the model (70–80% of surface motion recaptured), substantial differences in subsurface deformation occurs suggesting that subsurface validation of model-guided techniques will be important for advancing this concept.